Dietary management of peanut and tree nut allergy: what exactly should patients avoid?. Issue 5 (May 2015) - Brough, H. A.; Turner, P. J.; Wright, T.; Fox, A. T.; Taylor, S. L.; Warner, J. O.; Lack, G.
Summary Peanut and tree nut allergies are the commonest cause of life‐threatening food‐allergic reactions and significantly affect quality of life in children and their families. Dietary nut avoidance and provision of emergency medication is currently the mainstay of treatment. Nut avoidance has consequences on both quality of life and nutrition. We review the terminology that may cause confusion and lead to unnecessary dietary restrictions. In peanut or tree nut‐allergic children, introduction of specific nuts to which the child is not allergic may improve quality of life and should be considered in patients with multiple foods allergies, vegan or ethnic‐specific diets, in whom nuts are an important source of protein. Nut‐allergic consumers do not just need to avoid foods containing nuts as an ingredient, but also contend with pre‐packed foods which frequently have precautionary allergen labelling (PAL) referring to possible nut contamination. Although the published rate of peanut contamination in 'snack' foods with PAL (see Box 1) ranges from 0.9–32.4%, peanut contamination in non‐snack items with PAL is far less common. We propose that in some peanut‐allergic patients (depending on history of reactivity to trace levels of peanut, reaction severity, other medical conditions, willingness to always carry adrenaline, etc.), consideration may be given to allow the consumption of non‐snack foods containing PAL following discussion with the patient's (and their family's) specialist. More work is needed to provide consumers with clearer information on the risk of potential nut contamination in pre‐packed food. We also draw attention to the change in legislation in December 2014 that require mandatory disclosure of allergens in non‐pre‐packed foods.